2019
DOI: 10.1002/chem.201900236
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Alkali Metal Ions on the Stability and Reactivity of Chromium(III) Superoxide Moieties Spanned by Siloxide Ligands

Abstract: In recent years, it has become clear that the presence of redox‐inactive Lewis acidic metal ions can decisively influence the reactivity of metal–dioxygen moieties that are formed in the course of O2 activation, in molecular complexes, and metalloenzymes. Superoxide species are often formed as the primary intermediates but they are mostly too unstable for a thorough investigation. We report here a series of chromium(III) superoxide complexes [L2Cr]M2O2(THF)y (L=−OSiPh2OSiPh2O−, M+=Li+, Na+, K+ and y=4, 5), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 56 publications
5
38
0
Order By: Relevance
“…X‐ray analysis led to the structure of [L 2 Cr 2 (O 2 ) 2 ][Li(MeCN)] 2 ( 7 ) revealing that each chromium center is binding one O 2 molecule in a side‐on fashion (Figure 2). The O−O bond distance of 1.346(9) Å is in good agreement with values previously observed for chromium siloxide complexes with end‐on bound superoxo ligands (1.334(7), 1.324(7) and 1.334(4) Å) [5,8] …”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…X‐ray analysis led to the structure of [L 2 Cr 2 (O 2 ) 2 ][Li(MeCN)] 2 ( 7 ) revealing that each chromium center is binding one O 2 molecule in a side‐on fashion (Figure 2). The O−O bond distance of 1.346(9) Å is in good agreement with values previously observed for chromium siloxide complexes with end‐on bound superoxo ligands (1.334(7), 1.324(7) and 1.334(4) Å) [5,8] …”
Section: Methodssupporting
confidence: 89%
“…Both the position of the bands and the isotopic shift of Δ( 16 O− 18 O)=51 cm −1 are typical for chromium bound superoxo ligands (Figure 3). [4a,5,8–9] From these results it can be concluded that the reaction of 5 with dioxygen involves the formation of the dinuclear Cr III superoxo complex 7 as an intermediate (Scheme 3). The formation of such a complex is very uncommon, as typically upon activation of the first O 2 molecule at one metal center of a dinuclear complex the superoxo entity thus formed immediately reacts/interacts with the second metal center in close proximity.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Bearing in mind recent results, which we had obtained with analogous complexes containing chromium(II) as central metal ion, [L 2 Cr][M(Solv) 2 ] 2 (M=Li, Na, K), [12] the O 2 reactivity of [L 2 Fe][M(Solv) 2 ] 2 shifted into our focus, as there is a relation between chromium and iron: chromium(II) in contact with O 2 often forms intermediates comparable to those formed by corresponding iron(II) compounds, however, the Cr/O 2 adducts are often somewhat more stable and can thus be investigated in more detail, thus providing an idea on the proceedings in case of the corresponding iron analogues. [13] For the complexes (M=Li, Na, K) in contact with O 2 we had been able to show that chromium(III) superoxides are formed and that their stability and reactivity is dependent on the alkali metal ions M + , as these were found to interact with the superoxide ligand.…”
Section: Resultsmentioning
confidence: 94%